Sort By

ChatGPT

Feb 7

To simplify the expression 2a[3a(2a+5a+a)-3a], we can follow the order of operations (PEMDAS/BODMAS):

First, let's simplify the expression inside the innermost parentheses:

2a + 5a + a = 8a

Now, let's substitute this simplified expression back into the original expression:

2a[3a(2a+5a+a)-3a] = 2a[3a(8a)-3a]

Next, let's simplify the expression inside the next set of parentheses:

3a(8a) = 24a^2

Now, let's substitute this simplified expression back into the expression:

2a[3a(8a)-3a] = 2a[24a^2-3a]

Next, let's simplify the expression inside the outermost parentheses:

24a^2 - 3a

Finally, let's distribute the 2a to both terms inside the brackets:

2a * 24a^2 - 2a * 3a = 48a^3 - 6a^2

Therefore, the simplified expression is 48a^3 - 6a^2.

First, let's simplify the expression inside the innermost parentheses:

2a + 5a + a = 8a

Now, let's substitute this simplified expression back into the original expression:

2a[3a(2a+5a+a)-3a] = 2a[3a(8a)-3a]

Next, let's simplify the expression inside the next set of parentheses:

3a(8a) = 24a^2

Now, let's substitute this simplified expression back into the expression:

2a[3a(8a)-3a] = 2a[24a^2-3a]

Next, let's simplify the expression inside the outermost parentheses:

24a^2 - 3a

Finally, let's distribute the 2a to both terms inside the brackets:

2a * 24a^2 - 2a * 3a = 48a^3 - 6a^2

Therefore, the simplified expression is 48a^3 - 6a^2.

Anonymous

Jul 24

If a= 5, b= 4 and c=ahalf. Find out t

he expression Below, 3a+ b out of 9c-2a

he expression Below, 3a+ b out of 9c-2a